Molecular structure, experimental and theoretical 1H and 13C NMR chemical shift assignment of cyclic and acyclic Î±, Î²âunsaturated esters. (17th November 2013) - Buceta, Norma N.; Ruiz, Diego; Romanelli, Gustavo P.; Autino, Juan C.; Duddeck, Helmut; Pis Diez, Reinaldo; Jios, Jorge L.
<x xml:space="preserve">Abstract</x> The experimental 1H and 13C NMR spectra of 13 phenyl cinnamates and four 4âmethylcoumarins were investigated and their chemical shifts assigned on the basis of the twoâdimensional spectra. For the unsubstituted cinnamic acid phenyl ester, optimized molecular structures were calculated at a B3LYP/6â311++G(d, p) level of theory. 1H and 13C NMR chemical shifts were also calculated with the GIAO method at the B3LYP/6â311â+âG(2d, p) level of theory. The comparison between experimental and calculated NMR chemical shift suggests that the experimental spectra are formed from the superposition spectra of the two lowest energy conformers of the compound in solution. The most stable sâcis configuration found in our studies is also the conformation adopted for a related phenyl cinnamate in solid state. The experimental results were analyzed in terms of the substituent effects. Copyright Â© 2013 John Wiley & Sons, Ltd.